Pengembangan Lembar Aktivitas Murid Berorientasi Problem Based Learning untuk Melatihkan Keterampilan Berpikir Kritis pada materi Hidrolisis Garam - Nova Apriliyaningtias; Bertha Yonata (UNIB Press, 2026)
This study aimed to develop a Problem-Based Learning-oriented Student Activity Sheet on the topic of salt hydrolysis and to determine its suitability for fostering students' critical thinking skills. The study employed the Research and Development (R&D) method using the 4D model—comprising the define, design, develop, and disseminate stages—though implementation was limited to the development stage. A limited trial involved 20 Phase F students at SMA Widya Darma Surabaya. Data were collected via validation sheets, student response questionnaires, student activity observation sheets, critical thinking skills tests, and knowledge tests. Analysis revealed that the product achieved a validity mode of 4, falling into the